Association between MKL1 rs6001946 and schizophrenia in a Han Chinese population. (19th September 2016) - Wang, Dong; Cheng, Zaohuo; Zhao, Xingfu; Li, Zongchang; Wang, Jun; Dong, Aiguo; Zhou, Zhenhe; Zhang, Fuquan
Highlights: MKL1 rs1344706 is a promising risk variant identified for schizophrenia by a genome-wide association study. This study showed that SNP rs6001946 within the MKL1 gene was marginally associated with schizophrenia in Han Chinese. Future research should be warranted to confirm the association between MKL1 and schizophrenia. Abstract: Megakaryoblastic leukemia 1 (MKL1) is highly expressed in the nervous system and plays a potentially principal role in neuronal migration and morphology. A recent study showed that some genetic loci within the MKL1 gene, especially single nucleotide polymorphism (SNP) rs6001946, may increase schizophrenia susceptibility. Here, we sought to determine whether the polymorphism rs6001946 was associated with schizophrenia in a Han Chinese population using the ligase detection reaction–polymerase chain reaction method to genotype SNP rs6001946 in the MKL1 gene. We observed that there was a marginally significant association between SNP rs6001946 and the risk of schizophrenia (P = 0.077). Our results indicated that SNP rs6001946 of the MKL1 gene is likely a risk factor for schizophrenia, but the role of SNP rs6001946 in the development of schizophrenia in Han Chinese should be interpreted cautiously. Further studies with larger sample sizes are needed to determine the involvement of the MKL1 polymorphism in schizophrenia susceptibility.